CFD ANALYSIS OF SMOKE AND TEMPERATURE CONTROL SYSTEM OF AN INDOOR PARKING LOT WITH JET FANS - Senveli, A.; Dizman, T.; Celen, A.; Bilge, D.; Dalkilic, A. S.; Wongwises, S. (YILDIZ TECHNICAL UNIV, 2015)
The aim of this study is to perform analysis and interpretation of daily emission ventilation and fire ventilation system design in indoor parking lots with jet fans with the help of CFD program. In the study, ventilation of 8-story parking lot of a major business center in Istanbul with jet fans have been carried out, and the analysis on one story of this parking lot is provided as a case study. The airflow in all the regions of parking lot has been examined, the most suitable jet fan placements have been determined for daily emission and fire ventilation, and accuracy of this placement has been proved through the analysis with this study. The performed CFD analysis has enabled us to see correct placement of the jet fans and to intervene and decide the best placement. And for the fire case, the optimal results have been obtained by creating various scenarios in accordance with the international standards. It has been observed that the use of CFD analysis in the solution of the problem has allowed significant savings in time and money.
Keywords: Normal Pollution Ventilation (NPV); Computational Fluid Dynamics (CFD); Jet Fans; Impulse Ventilation; Smoke and Heat Control (SHC); Thermodynamics